Efficacy and Safety of 7-Day Non-Bismuth Concomitant Quadruple Therapy for First-Line Helicobacter pylori Eradication in the Elderly - Ma, Te-Ling; Tai, Wei-Chen; Loke, Song-Seng; Yao, Chih-Chien; Liang, Chih-Ming; Chuah, Seng-Kee (Drugs & aging, 2023)
Background Aging may affect the efficacy of Helicobacter pylori eradication. The aim of our study was to assess the efficacy and safety of 7-day non-bismuth concomitant quadruple therapy as a first-line H. pylori infection eradication regimen in elderly individuals. Methods We retrospectively analyzed a cohort with prospectively collected data from January 2013 to December 2019 at Chang Gung Memorial Hospital in Kaohsiung. There were 408 naive infected subjects aged 20 years or older who were treated with 7 days of concomitant therapy as a first-line H. pylori eradication regimen. We divided the patients into an elderly group (aged ≥ 65 years) and a control group (aged < 65 years). Two patients were lost during follow-up in the elderly group and 29 patients were lost in the control group, resulting in 56 in the ≥ 65-year age group and 321 in the control group. The patients were asked to perform urea breath tests 8 weeks later. Results The eradication rates for the elderly and control groups were 93.1% (95% confidence interval (CI): 83.3–98.1) and 84.0% (95% CI 79.7–87.7) ( p = 0.070), respectively, in the intention-to-treat analysis, and 96.4% (95% CI 87.6–99.6) and 91.6% (95% CI 88.0–94.4) ( p = 0.210), respectively, in the per-protocol (PP) analysis. The adverse event rates were 8.9% in the elderly group and 12.8% in the control group ( p = 0.417). The compliance was 100% in both groups. No significant difference was seen in antibiotic resistance in either group. Multivariate analysis revealed that metronidazole resistance (odds ratio (OR) 6.870, 95% CI 1.182–39.919, p = 0.032) and dual-therapy resistance (OR 7.188, 95% CI 1.326–38.952, p = 0.022) were independent factors for eradication failure. Conclusions The efficacy of non-bismuth concomitant quadruple therapy in the elderly cohort was comparable with that in the non-elderly cohort for first-line H. pylori eradication with acceptable adverse effects.